Preparation method of high-safety metal lithium battery diaphragm

By combining modified PAA microspheres and modified boehmite and other materials, a high-safe metal lithium battery separator was prepared, which solved the problem of insufficient safety of existing separators at high temperatures, significantly improved the safety and service life of lithium batteries, and improved the charging and discharging performance of the battery.

CN119742537AActive Publication Date: 2025-04-01YANCHENG TEACHERS UNIV

Patent Information

Application Number
CN202411828445.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-01
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

The existing lithium battery separators cannot guarantee safety at high temperatures, and there is a risk of shrinkage or damage, which affects the safety and service life of the lithium battery.

Method used

The microsphere slurry is prepared by ultrasonic dispersion and magnetic stirring, and then a high-safe metal lithium battery separator is dried in the blower oven to produce a high-safe metal lithium battery separator.

Benefits of technology

The heat resistance temperature of the diaphragm is improved, and the shrinkage or damage is prevented under high temperature conditions is enhanced, and the safety and service life of lithium batteries are enhanced. At the same time, the addition of modified boehmite enhances puncture resistance. Polyvinylidene fluoride and polymethyl methacrylate improves the absorption capacity of the electrolyte, reduces the internal resistance of the battery, and improves the charge and discharge performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742537A_ABST
    Figure CN119742537A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-safety metal lithium battery diaphragm, and relates to the technical field of lithium battery diaphragms.The preparation method comprises the following preparation steps that firstly, modified PAA microspheres, polyvinylpyrrolidone and sodium carboxymethyl cellulose are added into a mixed solvent, after ultrasonic dispersion is conducted for 20-30 min, stirring is conducted for 3.5-4 h at the rotating speed of 1200-1500 r / min through a magnetic stirrer, and then the modified PAA microspheres, the polyvinylpyrrolidone and the sodium carboxymethyl cellulose are obtained; microsphere slurry is obtained; and 2, coating the microsphere slurry on the two surfaces of the diaphragm at a gap of 80-100mm on an automatic blade coating machine, and then drying in a blast oven at 45-50 DEG C for 6-8 hours to obtain the high-safety metal lithium battery diaphragm. According to the preparation method of the high-safety metal lithium battery diaphragm, through the combined action of polyvinylidene fluoride modified boehmite, the heat-resistant temperature of the diaphragm is effectively improved, and the diaphragm is prevented from being shrunk or damaged under a high-temperature condition, so that the safety of a lithium battery is improved, and the service life of the lithium battery is prolonged; and the prepared diaphragm has good chemical stability and is not easily corroded by chemical substances such as electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0003] The invention relates to the technical field of lithium battery separators, and in particular to a method for preparing a metal lithium battery separator with high safety. Background Art

[0004] The Chinese patent with publication number CN104051694A discloses a lithium polyoxometalate composite diaphragm for lithium batteries and its preparation method. The composite diaphragm includes PVDF-HFP copolymer, SiO2 and lithium polyoxometalate. The lithium polyoxometalate has a three-dimensional skeleton structure. The lithium ions are combined with the anions of the lithium polyoxometalate. During the battery charging and discharging process, the lithium ions of the lithium polyoxometalate can continuously exchange with the lithium ions in the electrolyte, realizing the combination of the diaphragm material and the lithium ions in the electrolyte, reducing the internal resistance of the battery and improving the rate characteristics of the battery. However, the battery diaphragm prepared by the above-mentioned prior art solution cannot guarantee safety under high temperature conditions; for this reason, the present invention provides a method for preparing a highly safe metal lithium battery diaphragm to solve the above problems. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a method for preparing a metal lithium battery separator with high safety, which solves the problems mentioned in the above background technology.

[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for preparing a highly safe metal lithium battery separator, comprising the following preparation steps:

[0007] Step 1: Add modified PAA microspheres, polyvinyl pyrrolidone and sodium carboxymethyl cellulose to a mixed solvent, disperse by ultrasonic for 20-30 minutes, and stir with a magnetic stirrer at a speed of 1200-1500 r / min for 3.5-4 hours to obtain a microsphere slurry;

[0008] Step 2: On an automatic scraper coater, the microsphere slurry is coated on both sides of the diaphragm with a gap of 80-100 mm, and then placed in a blast oven at 45-50°C for 6-8 hours to obtain a highly safe metal lithium battery diaphragm.

[0009] Preferably, the weight proportions of the components added in the metal lithium battery separator are: 8-15 parts of modified PAA microspheres, 0.5-2 parts of polyvinyl pyrrolidone, 0.5-2 parts of sodium carboxymethyl cellulose, and 25-45 parts of mixed solvent.

[0010] Preferably, in step 1, the mixed solvent is prepared by deionized water and anhydrous ethanol, and the volume ratio of deionized water to anhydrous ethanol is 1:(0.8-1.5).

[0011] Preferably, the preparation method of the diaphragm is:

[0012] (1) 15-20 g of polyvinylidene fluoride and 3.5-6 g of polymethyl methacrylate were placed in a vacuum drying oven at 60-70° C. and dried for 10-12 h;

[0013] (2) Pour 60-70 mL of N,N-dimethylformamide into the mixture, heat the mixture in a water bath to 35-45° C., stir mechanically for 8-10 h, add 0.8-1.2 g of modified boehmite, continue stirring, and let stand for 40-60 min after mixing evenly to obtain a spinning solution;

[0014] (3) Turn on the heating lamp of the spinning machine, use a syringe to extract the spinning solution, and start spinning when the humidity in the spinning machine chamber drops to 20% RH and the temperature is 40-45°C. After spinning is completed, place it in a vacuum drying oven at 50-60°C and dry it for 10-14 hours to obtain a diaphragm.

[0015] Preferably, the spinning voltage is 15-25 kV, the liquid pushing speed is 0.002-0.004 mm / s, and the receiving distance is 16-18 cm.

[0016] Preferably, the preparation method of the modified boehmite is: 25-30g of boehmite is placed in a drying oven for drying, then poured into 50-65g of KH550, ultrasonically treated for 20-30min, heated to 130-150°C, and stirred and refluxed at this temperature for 1.5-2h, the product is washed with deionized water until the supernatant is neutral, and then placed in a drying oven at 50-60°C for drying to obtain the modified boehmite.

[0017] Preferably, the preparation method of the modified PAA microspheres is:

[0018] S1. Heat the PAA microspheres in a blast oven at 260-300°C for 1.5-2.5 hours, and then soak them in a 0.2 mol / L sodium hydroxide solution for 10-20 minutes.

[0019] S2, after washing with deionized water for 3-5 times, immerse in 3w% acetic acid solution for 20-30min;

[0020] S3. Take out and continue washing with deionized water for 3-5 times to obtain modified PAA microspheres.

[0021] Preferably, the preparation method of the PAA microspheres is:

[0022] S11. Pour 35-50 mL of N,N-dimethylformamide into a mixed solution of 10-12.5 g of pyromellitic anhydride and 8.5-10 g of 4,4′-diaminodiphenyl ether under ice bath conditions at 0-2°C;

[0023] S12, heating to 50-60°C and reacting at this temperature for 40-48h;

[0024] S13. Electrostatic spraying is performed under the parameter conditions of positive pressure 15-20 kV and negative pressure 4-6 kV to obtain PAA microspheres.

[0025] Beneficial Effects

[0026] The present invention provides a method for preparing a highly safe metal lithium battery separator. Compared with the prior art, it has the following beneficial effects:

[0027] (1) The method for preparing the high-safety metal lithium battery diaphragm effectively improves the heat resistance temperature of the diaphragm through the combined effect of polyvinylidene fluoride modified boehmite, prevents the diaphragm from shrinking or being damaged under high temperature conditions, thereby improving the safety and service life of the lithium battery; and the prepared diaphragm has good chemical stability and is not easily corroded by chemical substances such as electrolyte, which can ensure that the performance of the diaphragm does not significantly decrease during long-term use; the addition of modified boehmite can enhance the puncture resistance of the diaphragm, prevent the diaphragm from being punctured due to the expansion of the positive and negative electrode materials inside the battery or other reasons, thereby avoiding safety problems such as short circuit caused by direct contact between the positive and negative electrodes, and improving the safety of the diaphragm during use; polyvinylidene fluoride and polymethyl methacrylate have good affinity with the electrolyte, can effectively absorb and retain the electrolyte, N, N-dimethylformamide as a solvent can make the components fully mixed, which is conducive to forming a stable electrolyte system, thereby improving the ionic conductivity, reducing the internal resistance of the battery, and improving the battery's charge and discharge performance and rate performance.

[0028] (2) The preparation method of the high-safety metal lithium battery separator can modify the PAA microspheres to deprotonate the carboxyl groups on the surface of the PAA microspheres, increase their hydrophilicity, make them easier to absorb and retain electrolytes, thereby improving ionic conductivity, reducing battery internal resistance, and improving battery charge and discharge performance and rate performance. At the same time, the surface properties of the PAA microspheres can be adjusted to further optimize their affinity with the electrolyte, ensuring that the separator can stably retain the electrolyte during the charge and discharge process and provide a good dielectric environment for the transmission of lithium ions; the modified PAA microspheres can better interact with other components in the separator material to form a stable network structure, thereby improving the tensile strength and tear resistance of the separator, so that it can withstand greater external forces during the assembly and use of the battery, is not easy to be damaged, and extends the service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The SEM images of PAA microspheres before and after modification provided by this paper;

[0030] Figure 2The infrared spectra of boehmite before and after modification provided by the present invention;

[0031] Figure 3 A comparison chart of thermal dimensional stability tests of the lithium battery separator provided by the present invention;

[0032] Figure 4 A comparison chart of high temperature safety tests of assembled batteries of Example 1 and Comparative Example 1 provided by the present invention. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] A method for preparing a highly safe metal lithium battery separator comprises the following preparation steps:

[0036] Step 1: add 8 g of modified PAA microspheres, 2 g of polyvinyl pyrrolidone, and 2 g of sodium carboxymethyl cellulose to 45 g of a mixed solution of deionized water and anhydrous ethanol in a volume ratio of 1:0.8, and after ultrasonic dispersion for 20 min, stir with a magnetic stirrer at a speed of 1200 r / min for 3.5 h to obtain a microsphere slurry;

[0037] The preparation method of the diaphragm is as follows: 15g of polyvinylidene fluoride and 3.5g of polymethyl methacrylate are placed in a vacuum drying oven at 60°C and dried for 10h; then poured into 60mL of N,N-dimethylformamide, heated to 35°C in a water bath, mechanically stirred for 8h, 0.8g of modified boehmite is added, and stirring is continued. After the mixture is evenly mixed, it is allowed to stand for 40min to obtain a spinning solution; the heating lamp of the spinning machine is turned on, and the spinning solution is extracted with a syringe. When the humidity in the spinning machine chamber is reduced to 20%RH and the temperature is 40°C, spinning is started, the spinning voltage is 15kV, the liquid pushing speed is 0.002mm / s, and the receiving distance is 16cm. After the spinning is completed, it is placed in a vacuum drying oven at 50°C and dried for 10h to obtain the diaphragm;

[0038] The preparation method of modified boehmite is as follows: 25 g of boehmite is placed in a drying oven for drying, then poured into 50 g of KH550, ultrasonically treated for 20 minutes, heated to 130° C., and stirred and refluxed at this temperature for 1.5 hours, the product is washed with deionized water until the supernatant is neutral, and then placed in a drying oven at 50° C. for drying to obtain modified boehmite;

[0039] The preparation method of modified PAA microspheres is as follows: under ice bath conditions of 0°C, 35 mL of N,N-dimethylformamide is poured into a mixed solution of 10 g of pyromellitic anhydride and 8.5 g of 4,4′-diaminodiphenyl ether; after heating to 50°C, react under the temperature conditions for 40 hours; electrostatic spraying is performed under the parameter conditions of positive pressure 15 kV and negative pressure 4 kV to obtain PAA microspheres; the PAA microspheres are placed in a blast oven at 260°C and heated for 1.5 hours, and then immersed in a sodium hydroxide solution with a concentration of 0.2 mol / L for 10 minutes; after washing with deionized water for 3 times, immersed in a 3w% acetic acid solution for 20 minutes; taken out, and continued to be washed with deionized water for 3 times to obtain modified PAA microspheres;

[0040] Step 2: On an automatic scraper coater, the microsphere slurry is coated on both sides of the diaphragm with a gap of 80 mm, and then placed in a blast oven at 45°C for 6 hours to obtain a highly safe metal lithium battery diaphragm.

[0041] Example 2

[0042] A method for preparing a highly safe metal lithium battery separator comprises the following preparation steps:

[0043] Step 1: add 12 g of modified PAA microspheres, 1 g of polyvinyl pyrrolidone, and 1.5 g of sodium carboxymethyl cellulose to 35 g of a mixed solution of deionized water and anhydrous ethanol in a volume ratio of 1:1, and ultrasonically disperse for 25 min, and then stir with a magnetic stirrer at a speed of 1300 r / min for 3.8 h to obtain a microsphere slurry;

[0044] The preparation method of the diaphragm is as follows: 17g of polyvinylidene fluoride and 4.5g of polymethyl methacrylate are placed in a vacuum drying oven at 65°C and dried for 11h; then poured into 65mL of N,N-dimethylformamide, heated to 40°C in a water bath, mechanically stirred for 9h, 1g of modified boehmite is added, and stirring is continued. After the mixture is evenly mixed, it is allowed to stand for 50min to obtain a spinning solution; the heating lamp of the spinning machine is turned on, and the spinning solution is extracted with a syringe. When the humidity in the spinning machine chamber is reduced to 20%RH and the temperature is 42°C, spinning is started, the spinning voltage is 20kV, the liquid pushing speed is 0.003mm / s, and the receiving distance is 17cm. After the spinning is completed, it is placed in a vacuum drying oven at 55°C and dried for 12h to obtain the diaphragm;

[0045] The preparation method of the modified boehmite is as follows: 28 g of boehmite is placed in a drying oven for drying, then poured into 60 g of KH550, ultrasonically treated for 25 minutes, heated to 140° C., and stirred and refluxed at this temperature for 1.8 hours, the product is washed with deionized water until the supernatant is neutral, and then placed in a drying oven at 55° C. for drying to obtain the modified boehmite;

[0046] The preparation method of modified PAA microspheres is as follows: under the condition of 1°C ice bath, 40mL of N,N-dimethylformamide is poured into a mixed solution of 11.5g of pyromellitic anhydride and 9g of 4,4′-diaminodiphenyl ether; after heating to 55°C, react under the temperature condition for 44h; electrostatic spraying is performed under the parameter conditions of positive pressure 18kV and negative pressure 5kV to obtain PAA microspheres; the PAA microspheres are placed in a blast oven at 280°C and heated for 2h, and then immersed in a sodium hydroxide solution with a concentration of 0.2mol / L for 15min; after washing with deionized water for 4 times, immersed in a 3w% acetic acid solution and treated for 25min; taken out and continued to be washed with deionized water for 4 times to obtain modified PAA microspheres;

[0047] Step 2: On an automatic scraper coater, the microsphere slurry is coated on both sides of the diaphragm with a gap of 90 mm, and then placed in a blast oven at 48°C for 7 hours to obtain a highly safe metal lithium battery diaphragm.

[0048] Example 3

[0049] A method for preparing a highly safe metal lithium battery separator comprises the following preparation steps:

[0050] Step 1: add 15 g of modified PAA microspheres, 0.5 g of polyvinyl pyrrolidone, and 0.5 g of sodium carboxymethyl cellulose to 25 g of a mixed solution of deionized water and anhydrous ethanol in a volume ratio of 1:0.8, and ultrasonically disperse for 30 min, and then stir for 4 h with a magnetic stirrer at a speed of 1500 r / min to obtain a microsphere slurry;

[0051] The preparation method of the diaphragm is as follows: 20g of polyvinylidene fluoride and 6g of polymethyl methacrylate are placed in a vacuum drying oven at 70°C and dried for 12h; then poured into 70mL of N,N-dimethylformamide, heated to 45°C in a water bath, mechanically stirred for 10h, 1.2g of modified boehmite is added, and stirring is continued. After the mixture is evenly mixed, it is allowed to stand for 60min to obtain a spinning solution; the heating lamp of the spinning machine is turned on, and the spinning solution is extracted with a syringe. When the humidity in the spinning machine chamber is reduced to 20%RH and the temperature is 45°C, spinning is started, the spinning voltage is 25kV, the liquid pushing speed is 0.004mm / s, and the receiving distance is 18cm. After the spinning is completed, it is placed in a vacuum drying oven at 60°C and dried for 14h to obtain the diaphragm;

[0052] The preparation method of modified boehmite is as follows: 30 g of boehmite is placed in a drying oven for drying, then poured into 65 g of KH550, ultrasonically treated for 30 minutes, heated to 150° C., and stirred and refluxed at the temperature for 2 hours, the product is washed with deionized water until the supernatant is neutral, and then placed in a drying oven at 60° C. for drying to obtain modified boehmite;

[0053] The preparation method of modified PAA microspheres is as follows: under an ice bath condition of 2°C, 50 mL of N,N-dimethylformamide is poured into a mixed solution of 12.5 g of pyromellitic anhydride and 10 g of 4,4′-diaminodiphenyl ether; after heating to 60°C, react under the temperature condition for 48 hours; electrostatic spraying is performed under the parameter conditions of positive pressure 20 kV and negative pressure 6 kV to obtain PAA microspheres; the PAA microspheres are placed in a blast oven at 300°C and heated for 2.5 hours, and then immersed in a sodium hydroxide solution with a concentration of 0.2 mol / L for 20 minutes; after washing with deionized water for 5 times, immersed in a 3w% acetic acid solution and treated for 30 minutes; taken out and continued to be washed with deionized water for 5 times to obtain modified PAA microspheres;

[0054] Step 2: On an automatic scraper coater, the microsphere slurry is coated on both sides of the diaphragm with a gap of 100 mm, and then placed in a blast oven at 50° C. to dry for 8 hours to obtain a highly safe metal lithium battery diaphragm.

[0055] Comparative Example 1

[0056] Compared with Example 1, the difference is that the modified PAA microspheres in Example 1 are replaced by PAA microspheres; the rest remains unchanged.

[0057] Comparative Example 2

[0058] Compared with Example 1, the difference is that the modified boehmite in Example 1 is replaced by boehmite; the rest remains unchanged.

[0059] like Figure 1 As shown in the figure, the surface of the PAA microspheres before modification is smooth, and the spherical structure is complete and round, and the particle size distribution is uniform. The surface of the PAA microspheres after modification is no longer smooth, but becomes extremely rough, with many cracks and spots. This is because the etching of the alkaline solution destroys the amide ring in the molecule, resulting in many rough spots on the surface of the microspheres but does not destroy the spherical structure of the microspheres. Only the ring is opened on the surface of the microspheres, thereby introducing the -COOH structure.

[0060] like Figure 2 As shown, boehmite has a peak at 1384 cm -1 The absorption peaks before and after are the overtone bands of the surface hydroxyl groups; and at 3500cm -1 The left and right are the strong hydroxyl absorption peaks on the surface of boehmite; the stretching vibration peak of A1-O6 is located at 502cm -1 and 615cm -1 The OH vibration peaks are located at 739 cm -1 、1070cm -1 、3097cm -1 and 3308cm -1Modified boehmite, 2927cm -1 and 2850cm -1 The peak at is the stretching vibration peak of CH in CH, and the CH2 group comes from the silane coupling agent, which indicates that the aluminum hydroxyl group of boehmite and the alkoxy group of the silane coupling agent undergo a condensation reaction, and the coupling agent is successfully grafted onto boehmite.

[0061] Electrochemical impedance test: Use a diaphragm punching machine to cut a lithium battery diaphragm with a diameter of 16 mm, and measure the thickness with a thickness gauge. Then put it in a vacuum oven at 60°C for 10 hours. In a glove box, CR2023 button batteries are assembled in the order of positive and negative electrodes being stainless steel sheets and electrolyte being LPF6 / (EC, DEC, DMC=1:1:1). After the battery is assembled, let it stand for 12 hours. Select the AC impedance mode in the electrochemical workstation, set the amplitude to 5mV, the frequency range to 1-10KHz, and the equilibrium time to 2s; the results are shown in Table 1; the ionic conductivity formula is:

[0062]

[0063] Where σ is the ionic conductivity, mS / cm; d is the thickness of the diaphragm, cm; R b is the internal resistance of the diaphragm, Ω; A S is the contact area between the diaphragm and the stainless steel electrode, cm 2 .

[0064] Mechanical properties test: The lithium battery separator was cut into 20mmx150mm film strips and clamped in a mold. The tensile strength and elongation at break of the film were measured using an XLW intelligent electronic tensile testing machine. The test conditions were: tensile rate 25mm / min, test temperature 23+2°C, test humidity 50+5%. The results are shown in Table 1.

[0065] Table 1

[0066] Ionic conductivity (mS / cm) Tensile strength / MPa Elongation at break / % Example 1 1.032 51.37 24.68 Example 2 1.035 50.86 24.09 Example 3 1.031 51.22 24.46 Comparative Example 1 0.816 45.31 19.03 Comparative Example 2 0.749 47.85 21.54

[0067] Thermal dimensional stability test: First, the lithium battery separator was cut into a circle with a diameter of 15 mm, placed in an oven at 160°C, and the state was observed after 1 hour and 2 hours; the results are as follows Figure 3 As shown: compared with comparative examples 1-2, the lithium battery separators prepared in examples 1-3 only show slight shrinkage.

[0068] High temperature safety test: After the assembled button half-cell is left to stand for 12 hours, it is charged at a rate of 0.1C to a voltage of 4.3V, and then discharged at a rate of 0.1C in an oven at a constant temperature of 140°C; Figure 4As shown: the battery assembled in Comparative Example 1 showed an obvious voltage drop at around 22 minutes, and the voltage dropped to 0 at 27 minutes, indicating that a short circuit occurred inside the battery at this time; the battery assembled in Example 1 did not show an obvious voltage drop in the first 150 minutes, the voltage dropped rapidly at around 160 minutes, and the voltage dropped to 0 at 167 minutes, indicating that the battery assembled with the lithium battery diaphragm in Example 1 survived much longer than the battery assembled with the lithium battery diaphragm in Comparative Example 1 at a high temperature of 140°C, indicating that the battery assembled with the lithium battery diaphragm in Example 1 has excellent safety performance at high temperatures.

[0069] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.

[0070] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0071] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a highly safe metal lithium battery separator, characterized in that: The method comprises the following preparation steps: Step 1: Add modified PAA microspheres, polyvinyl pyrrolidone and sodium carboxymethyl cellulose to a mixed solvent, disperse by ultrasonic for 20-30 minutes, and stir with a magnetic stirrer at a speed of 1200-1500 r / min for 3.5-4 hours to obtain a microsphere slurry; Step 2: On an automatic scraper coater, the microsphere slurry is coated on both sides of the diaphragm with a gap of 80-100 mm, and then placed in a blast oven at 45-50°C for 6-8 hours to obtain a highly safe metal lithium battery diaphragm.

2. The method for preparing a highly safe metal lithium battery separator according to claim 1, characterized in that: The weight proportions of the components added in the metal lithium battery separator are: 8-15 parts of modified PAA microspheres, 0.5-2 parts of polyvinyl pyrrolidone, 0.5-2 parts of sodium carboxymethyl cellulose, and 25-45 parts of a mixed solvent.

3. The method for preparing a highly safe metal lithium battery separator according to claim 1, characterized in that: In the step 1, the mixed solvent is prepared by deionized water and anhydrous ethanol, and the volume ratio of deionized water to anhydrous ethanol is 1:(0.8-1.5).

4. The method for preparing a highly safe metal lithium battery separator according to claim 1, characterized in that: The preparation method of the diaphragm is as follows: (1) 15-20 g of polyvinylidene fluoride and 3.5-6 g of polymethyl methacrylate were placed in a vacuum drying oven at 60-70° C. and dried for 10-12 h; (2) Pour 60-70 mL of N,N-dimethylformamide into the mixture, heat the mixture in a water bath to 35-45° C., stir mechanically for 8-10 h, add 0.8-1.2 g of modified boehmite, continue stirring, and let stand for 40-60 min after mixing evenly to obtain a spinning solution; (3) Turn on the heating lamp of the spinning machine, use a syringe to extract the spinning solution, and start spinning when the humidity in the spinning machine chamber drops to 20% RH and the temperature is 40-45°C. After spinning is completed, place it in a vacuum drying oven at 50-60°C and dry it for 10-14 hours to obtain a diaphragm.

5. The method for preparing a highly safe metal lithium battery separator according to claim 4, characterized in that: in, The spinning voltage is 15-25 kV, the liquid pushing speed is 0.002-0.004 mm / s, and the receiving distance is 16-18 cm.

6. The method for preparing a highly safe metal lithium battery separator according to claim 1, characterized in that: The preparation method of the modified boehmite is as follows: 25-30 g of boehmite is placed in a drying oven for drying, then poured into 50-65 g of KH550, ultrasonically treated for 20-30 min, heated to 130-150° C., stirred and refluxed at the temperature for 1.5-2 h, the product is washed with deionized water until the supernatant is neutral, and then placed in a drying oven at 50-60° C. for drying to obtain the modified boehmite.

7. The method for preparing a highly safe metal lithium battery separator according to claim 1, characterized in that: The preparation method of the modified PAA microspheres is: S1. Heat the PAA microspheres in a blast oven at 260-300°C for 1.5-2.5 hours, and then soak them in a 0.2 mol / L sodium hydroxide solution for 10-20 minutes. S2, after washing with deionized water for 3-5 times, immerse in 3w% acetic acid solution for 20-30min; S3. Take out and continue washing with deionized water for 3-5 times to obtain modified PAA microspheres.

8. The method for preparing a highly safe metal lithium battery separator according to claim 7, characterized in that: The preparation method of the PAA microspheres is: S11. Pour 35-50 mL of N,N-dimethylformamide into a mixed solution of 10-12.5 g of pyromellitic anhydride and 8.5-10 g of 4,4′-diaminodiphenyl ether under ice bath conditions at 0-2°C; S12, heating to 50-60°C and reacting at this temperature for 40-48h; S13. Electrostatic spraying is performed under the parameter conditions of positive pressure 15-20 kV and negative pressure 4-6 kV to obtain PAA microspheres.

Citation Information

Patent Citations

  • Lithium polyoxometallate composite diaphragm for lithium battery

    CN104051694A

  • Preparation method of battery diaphragm

    CN104466064A

  • Polyimide coating modified polyolefin composite diaphragm and preparation method thereof

    CN113969006A

  • High-flame-retardant diaphragm for lithium ion battery and preparation method of high-flame-retardant diaphragm

    CN117543161A

  • Lithium ion battery separator

    JP2018032537A

Cited By

  • Lithium ion battery diaphragm and preparation method thereof

    CN120581832A